A GPR18‐based signalling system regulates IOP in murine eye. (27th May 2013) - Caldwell, Meggie D.; Hu, Sherry Shu‐Jung; Viswanathan, Suresh; Bradshaw, Heather; Kelly, Melanie EM; Straiker, Alex
<x xml:space="preserve">Abstract</x> Background and Purpose GPR18 is a recently deorphaned lipid receptor that is activated by the endogenous lipid N‐arachidonoyl glycine (NAGly) as well the behaviourally inactive atypical cannabinoid, abnormal cannabidiol (Abn‐CBD). The presence and/or function of any GPR18‐based ocular signalling system remain essentially unstudied. The objectives of this research are: (i) to determine the disposition of GPR18 receptors and ligands in anterior murine eye, (ii) examine the effect of GPR18 activation on intraocular pressure (IOP) in a murine model, including knockout mice for CB1, CB2 and GPR55. Experimental Approach IOP was measured in mice following topical application of Abn‐CBD, NAGly or the GPR55/GPR18 agonist O‐1602, alone or with injection of the GPR18 antagonist, O‐1918. GPR18 protein localization was assessed with immunohistochemistry. Endocannabinoids were measured using LC/MS‐MS. Key Results GPR18 protein was expressed most prominently in the ciliary epithelium and the corneal epithelium and, interestingly, in the trabecular meshwork. The GPR18 ligand, NAGly, was also detected in mouse eye at a level comparable to that seen in the brain. Abn‐CBD and NAGly, but not O‐1602, significantly reduced IOP in all mice tested. The antagonist, O‐1918, blocked the effects of Abn‐CBD and NAGly. Conclusions and Implications We present evidence for a functional GPR18‐based signalling system in the murine anterior eye, including receptors and ligands. GPR18 agonists, Abn‐CBD and NAGly, reduce IOP independently of CB1, CB2 or GPR55. These findings suggest that GPR18 may serve as a desirable target for the development of novel ocular hypotensive medications. Linked Articles This article is part of a themed section on Cannabinoids. To view the other articles in this section visit http://dx.doi.org/10.1111/bph.2013.169.issue‐4 & http://dx.doi.org/10.1111/bph.2012.167.issue‐8